2013
DOI: 10.1021/ja311850u
|View full text |Cite
|
Sign up to set email alerts
|

Turning a Kinase Deoxyribozyme into a Sensor

Abstract: The vast majority of deoxyribozyme-based sensors are designed using modified RNA-cleaving deoxyribozymes and detect analytes that act as allosteric regulators of their catalytic activity. These sensors are susceptible to background signals due to catalytic activity in the absence of target or contaminant molecules that cleave the RNA substrate, mimicking the deoxyribozyme reaction. In this manuscript, we introduce a novel system that avoids these problems by using the analyte as the substrate for a deoxyribozy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 50 publications
0
49
0
Order By: Relevance
“…15 The sequence programmability, automated controllable synthesis, high stability and intrinsic functionalities make DNA nanostructures advantageous over other counterparts in many biomedical applications. Conventional approaches to DNA nanostructure construction typically rely on Watson-Crick base-pairing between short DNA building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…15 The sequence programmability, automated controllable synthesis, high stability and intrinsic functionalities make DNA nanostructures advantageous over other counterparts in many biomedical applications. Conventional approaches to DNA nanostructure construction typically rely on Watson-Crick base-pairing between short DNA building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…Deoxyribozymes are specific DNA sequences with catalytic activity that have been used to catalyze a variety of reactions, 7 including self-5′-phosphorylation. 8 We have initiated a research program to use deoxyribozymes to perform covalent modification of amino acid side chains in peptide and protein substrates. 9 In the present study, we report that deoxyribozymes can be identified for phosphorylation of tyrosine residues in peptide substrates, using as the phosphoryl donor either a 5′-triphosphorylated RNA oligonucleotide (pppRNA) or guanosine 5′-triphosphate (GTP).…”
mentioning
confidence: 99%
“…The first example, reported by Andrew Ellington's group in 2005, used a two‐piece DNA assembly with an ATP‐dependent DNA‐ligating DNAzyme and its substrate arranged in a special way such that binding of ATP to the aptamer domain activates the ligase DNAzyme, which creates the needed circular DNA template for subsequent RCA reaction . The second example of making the requisite circular template for RCA was reported by our group, with a goal of detecting guanosine‐5′‐triphosphates (GTP) . In this case, a self‐phosphorylating DNAzyme first transfers a γ‐phosphate from GTP to the 5′‐end of the DNAzyme.…”
Section: Isothermal Amplification Of the Action Of Rna‐cleaving Dnazymesmentioning
confidence: 99%